Patients with Type 2 Diabetes Mellitus Accompanied by Elevated Serum CA19-9 Associated Not with Pancreatic Cancer but Interstitial Lung Disease - Shuichi Okada; Junichi Okada; Koji Kikkawa; Eijiro Yamada; Kazuya Okada; Kihachi Ohshima (Dubai Diabetes and Endocrinology Journal)
Introduction: CA19-9 is the most reliable tumor marker for pancreatic cancer, with 70–90% sensitivity, 90% specificity, 69% positive predictive value, and 90% negative predictive value. However, increased CA19-9 levels have been observed in benign conditions, pancreatitis, pulmonary disease, smoking, and hepatobiliary system disease. Numerous studies have reported that circulating CA19-9 levels are elevated during hyperglycemia in diabetes mellitus (DM) and have been associated with hemoglobin A1c (HbA1c). However, the precise mechanism behind increased serum CA19-9 levels in diabetes remains still unclear. Here, we report a case of type 2 DM (T2DM) accompanied by elevated serum CA19-9 levels due to not pancreatic cancer but interstitial pneumonitis. Case Report: The patient, a 73-year-old Japanese woman, was taking metformin (1,500 mg/day), repaglinide (1.5 mg/day), and sitagliptin (50 mg/day). Over the past year, she also took atorvastatin (5 mg/day) and azilsartan (40 mg/day). The patient had been followed up for systemic scleroderma (with low-dose steroid therapy) and mild interstitial lung disease (ILD) (without treatment) for a number of years at a different hospital. The patient’s peripheral blood laboratory findings were normal range. Her HbA1c level fluctuated between 7.0% and 8.0% in the past 6 months. Her CA19-9 level was fluctuated between 562.7 and 823.2 U/mL (normal <37), and her KL-6 level was fluctuated between 516 and 557 U/L (normal <500) in the past 6 months. Due to the marked increase in the CA19-9 level, an extensive screening examination was performed for malignancy, including abdominal ultrasound scan, computed tomography (CT), and magnetic resonance cholangiopancreatography, revealing no malignancy. We observed bilateral pulmonary lesions (bottom of lungs) and ground-glass opacity on the chest CT. The pancreatic monoclonal antigen type 2 (DU-PAN-2) level was <25 U/mL. Conclusions: In our case, CA19-9 levels were increased in association not with pancreatic cancer but with ILD. Thus, when T2DM is accompanied by elevated serum CA19-9 levels, attention needs to be paid not only to the presence of pancreatic cancer but also to the possible ILD. Especially, when diabetes and ILD are treated in different hospitals, diabetologists need to pay attention about the presence of hidden ILD besides DM.